(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
The transition toward a circular economy has become one of the most important strategies for ensuring sustainable economic growth, efficient resource utilization, and environmental protection. Biomass resources, particularly agricultural residues, livestock waste, and organic municipal waste, represent an important renewable resource capable of contributing to energy security and sustainable development. Uzbekistan, as an agricultural country, generates substantial quantities of biomass every year through cotton production, wheat cultivation, horticulture, livestock farming, and food-processing industries. However, a considerable share of these resources remains underutilized or is disposed of through environmentally